2004
DOI: 10.1016/j.atmosenv.2003.07.018
|View full text |Cite
|
Sign up to set email alerts
|

A reassessment of HOx South Pole chemistry based on observations recorded during ISCAT 2000

Abstract: Reported here are modeling results based on ISCAT (Investigation of Sulfur Chemistry of Antarctic Troposphere) 2000 observations recorded at the South Pole (SP) during the Austral Summer of 2000. The observations included a comprehensive set of photochemical parameters, e.g., NO, O 3 , and CO. It is worthy to note that not only were OH and HO 2 observed, but also HO x precursor species CH 2 O, H 2 O 2 , and HONO were measured. Previous studies have suggested that HONO is the major source of OH/HO x in the Arct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 37 publications
4
99
1
Order By: Relevance
“…It has been suggested that recorded levels of OH are a product of photochemical transformations at the snow-air interface. Molecules and radicals such as HCHO, [22] NO x , [23] HONO, [24] hydrogen peroxide, [25] higher aldehydes, [26] and HO 2 radicals, [27] produced by other photochemical processes taking place in the snowpack, are considered as sources of OH formation Measured levels of these compounds were used in calculations by a steady-state photochemical box model. [27,28] For data obtained in 2000 at the South Pole, model predictions of OH were accurate only in a certain range of NO levels.…”
Section: Unknown Sources Of Oh Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that recorded levels of OH are a product of photochemical transformations at the snow-air interface. Molecules and radicals such as HCHO, [22] NO x , [23] HONO, [24] hydrogen peroxide, [25] higher aldehydes, [26] and HO 2 radicals, [27] produced by other photochemical processes taking place in the snowpack, are considered as sources of OH formation Measured levels of these compounds were used in calculations by a steady-state photochemical box model. [27,28] For data obtained in 2000 at the South Pole, model predictions of OH were accurate only in a certain range of NO levels.…”
Section: Unknown Sources Of Oh Formationmentioning
confidence: 99%
“…Molecules and radicals such as HCHO, [22] NO x , [23] HONO, [24] hydrogen peroxide, [25] higher aldehydes, [26] and HO 2 radicals, [27] produced by other photochemical processes taking place in the snowpack, are considered as sources of OH formation Measured levels of these compounds were used in calculations by a steady-state photochemical box model. [27,28] For data obtained in 2000 at the South Pole, model predictions of OH were accurate only in a certain range of NO levels. [4,27] For data obtained at Summit, the discrepancy between model and measured values was found to depend strongly on meteorology: [6] when the wind was light (,6 m s À1 ) the measured value was twice the calculated values, whereas in high wind (.6 m s À1 ) and blowing snow the measured value was an order of magnitude higher than the calculated value.…”
Section: Unknown Sources Of Oh Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although measurement campaigns at the South Pole have confirmed low to negligible background concentrations of non-methane hydrocarbons (NMHCs), unexpectedly high concentrations of short-lived photochemical species have been observed. For example, elevated mixing ratios of ozone (O 3 ), NO y [1][2][3][4][5] and HO x [6][7][8] have been observed indicating that the South Pole boundary layer can be a highly oxidising environment. [7][8][9][10] NO x is emitted from the snowpack due to the photolysis of NO 3 À contained within the ice.…”
Section: Introductionmentioning
confidence: 99%
“…For example, elevated mixing ratios of ozone (O 3 ), NO y [1][2][3][4][5] and HO x [6][7][8] have been observed indicating that the South Pole boundary layer can be a highly oxidising environment. [7][8][9][10] NO x is emitted from the snowpack due to the photolysis of NO 3 À contained within the ice. [11][12][13] Other snowpack emissions have also been identified, such as HCHO and H 2 O 2 , within the interstitial air and in the overlying atmosphere across Antarctica and, specifically, at the South Pole.…”
Section: Introductionmentioning
confidence: 99%